THE IMPLEMENTATION OF PSAK NO.65: A SURVEY TOWARDS FAMILY BUSINESS DOMINATION IN INDONESIA - Eka Putri Pertiwi; Liana Rahardja (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2017)
This study examines the factor to assess control over an investee as the implementation of PSAK No. 65.  The research scope is level of share ownership as assessment of rights that give an investor power over an investee. Since most companies in Indonesia are family business, so the implementation of PSAK 65 is facing the challenge to be effective or not. The research sample used is 147 companies listed in IDX as of year 2015. We measure assessing control over an investee by the fulfillment of criterion whether shareholders either majority or minority have direct activities and controlled an investee as a board of management. The result shows tendency of bias in implementing PSAK 65 due to Indonesia’s business nature. It is found that 68% companies are heldby 11 closed related families. Still, the remaining 4 families are also “interrelated” that means far related families